Management of perforated diverticulitis with generalized peritonitis. A multidisciplinary review and position paper - Nascimbeni, R. (Tech Coloproctol, 2020)
Perforated diverticulitis is an emergent clinical condition and its management is challenging and still debated. The aim of this position paper was to critically review the available evidence on the management of perforated diverticulitis and generalized peritonitis in order to provide evidence-based suggestions for a management strategy. Four Italian scientific societies (SICCR, SICUT, SIRM, AIGO), selected experts who identified 5 clinically relevant topics in the management of perforated diverticulitis with generalized peritonitis that would benefit from a multidisciplinary review. The following 5 issues were tackled: 1) Criteria to decide between conservative and surgical treatment in case of perforated diverticulitis with peritonitis; 2) Criteria or scoring system to choose the most appropriate surgical option when diffuse peritonitis is confirmed 3); The appropriate surgical procedure in hemodynamically stable or stabilized patients with diffuse peritonitis; 4) The appropriate surgical procedure for patients with generalized peritonitis and septic shock and 5) Optimal medical therapy in patients with generalized peritonitis from diverticular perforation before and after surgery. In perforated diverticulitis surgery is indicated in case of diffuse peritonitis or failure of conservative management and the decision to operate is not based on the presence of extraluminal air. If diffuse peritonitis is confirmed the choice of surgical technique is based on intraoperative findings and the presence or risk of severe septic shock. Further prognostic factors to consider are physiological derangement, age, comorbidities, and immune status. In hemodynamically stable patients, emergency laparoscopy has benefits over open surgery. Options include resection and anastomosis, Hartmann’s procedure or laparoscopic lavage. In generalized peritonitis with septic shock, an open surgical approach is preferred. Non-restorative resection and/or damage control surgery appear to be the only viable options, depending on the severity of hemodynamic instability. Multidisciplinary medical management should be applied with the main aims of controlling infection, relieving postoperative pain and preventing and/or treating postoperative ileus. In conclusion, the complexity and diversity of patients with diverticular perforation and diffuse peritonitis requires a personalized strategy, involving a thorough classification of physiological derangement, staging of intra-abdominal infection and choice of the most appropriate surgical procedure.